The Feasibility of using Natural Rocks as Sources of Zinc and Cobalt Inlivestock Feeding in Ethiopia (Global Journal of Science Frontier Research, 2016)
In Ethiopia, feed industries are widely using limestone as a cheap source of Ca without adequate information on the bioavailability of its Ca content and the presence of useful minerals and toxic minerals as well. This being the case, the present study was conducted to determine the Zinc and Cobalt content of samples of limestone, Gypsum and marble powder collected from different parts of Ethiopia. Adequate quantities of lime stone, marble powder and gypsum were procured from different parts of Ethiopia and subjected to laboratory chemical analysis in triplicate. The results of this study clearly showed that the total ash content of all the materials analyzed in this study ranged between 81 and 99%, indicating the potential use of these materials (limestone, marble powder and gypsum) collected from different part of Ethiopia as supplementary mineral feed source in very small amounts. In present work the Zn content of the lime stone ranged (ppm) 18.4-50.8(with an average of 28.8),In marble powder ranged 16.3-58.88 (with an average of 37.59) and in that of Gypsum from Mugger cement was containing (an average of 10.87 the value of which was almost similar with the Zn content of Calcium-carbonate and calcite powder(21.33 ±1.20) and(37.50± 2.39%) respectively, showing that Zn content in gypsum of the present study is a beat lower than the content of limestone, marble powder and Calcite powder.
Keywords: gypsum powder; lime stone; livestock; marble powder; minerals